2022
DOI: 10.1080/13880209.2022.2131841
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of Gyeji-tang in a chronic obstructive pulmonary disease mouse model induced by cigarette smoke and lipopolysaccharide

Abstract: Context Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease associated with respiratory symptoms and narrowing of airways. Gyeji-tang (GJT) is a traditional Asian medicine that has been used to relieve early-stage cold symptoms, headache, and chills. Objective We examined the effect and potential molecular action mechanism of GJT in a mouse model of COPD induced by cigarette smoke (CS) plus lipopolysaccharide (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Yield, 88.6%; mp, 156.2− 157.9 °C. (6). To a solution of compound 5 (4.0 g, 0.013 mol) in DMSO, 40% HBr (8.50 mL) was added dropwise at 90 °C.…”
Section: -(3-amino-4-(benzyloxy)-2-hydroxyphenyl)ethan-1-one (4)mentioning
confidence: 99%
See 2 more Smart Citations
“…Yield, 88.6%; mp, 156.2− 157.9 °C. (6). To a solution of compound 5 (4.0 g, 0.013 mol) in DMSO, 40% HBr (8.50 mL) was added dropwise at 90 °C.…”
Section: -(3-amino-4-(benzyloxy)-2-hydroxyphenyl)ethan-1-one (4)mentioning
confidence: 99%
“…4 The chief pathophysiology of COPD is progressive inflammation, which is attributable to a progressive and irreversible decline in lung function associated with chronic bronchitis and airway obstruction as well as emphysema. 5,6 The pharmacotherapeutic strategies for COPD patients aim toward improving the symptoms, reducing the frequency and severity of exacerbations, improving the quality of life, and increasing tolerance to exercise. 7 The types of medications employed for the treatment of COPD include β 2 -agonists, muscarinic antagonists, inhaled corticosteroids, phosphodies-terase-4 (PDE4) inhibitors, and combination therapies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that matrix metalloproteinases (MMPs), which are pivotal proteolytic enzymes, are involved in pathological and inflammatory processes in several respiratory diseases, such as interstitial pneumonia [237] , pulmonary fibrosis [238] , and COPD [239] . In particular, MMP-1, MMP-2, MMP-8, and TIMP-1 have been demonstrated in experimental and clinical research to influence inflammation [240] , [241] , [242] .…”
Section: The Mechanism By Which La Ameliorates Respiratory Diseasesmentioning
confidence: 99%